2024
DOI: 10.1002/ctm2.1584
|View full text |Cite
|
Sign up to set email alerts
|

Tolerating CD47

Jeffrey S. Isenberg,
Enrique Montero

Abstract: Cluster of differentiation 47 (CD47) occupies the outer membrane of human cells, where it binds to soluble and cell surface receptors on the same and other cells, sculpting their topography and resulting in a pleiotropic receptor‐multiligand interaction network. It is a focus of drug development to temper and accentuate CD47‐driven immune cell liaisons, although consideration of on‐target CD47 effects remain neglected. And yet, a late clinical trial of a CD47‐blocking antibody was discontinued, existent trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 187 publications
0
4
0
Order By: Relevance
“…Further, Sim J et al showed that anti-human SIRPα Ab clone 21 enhanced cetuximab-induced ADCP both with and without Fc fragment of the anti-SIRPα Ab [ 38 ], suggesting the blocking of SIRPα-CD47 interaction is sufficient to enhance ADCP. It is well-known that SIRPα-CD47 interaction occurs both in trans and cis orientation, the latter occurs in monocytes and other myeloid cells where both SIRPα and CD47 are expressed on the same cell surface [ 9 , 19 , 39 ]. Despite the potential cis-interaction, DS-1103a successfully bound to human macrophages and enhanced the ADCP of Dato-DXd and T-DXd ( Fig 2B and 6A ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, Sim J et al showed that anti-human SIRPα Ab clone 21 enhanced cetuximab-induced ADCP both with and without Fc fragment of the anti-SIRPα Ab [ 38 ], suggesting the blocking of SIRPα-CD47 interaction is sufficient to enhance ADCP. It is well-known that SIRPα-CD47 interaction occurs both in trans and cis orientation, the latter occurs in monocytes and other myeloid cells where both SIRPα and CD47 are expressed on the same cell surface [ 9 , 19 , 39 ]. Despite the potential cis-interaction, DS-1103a successfully bound to human macrophages and enhanced the ADCP of Dato-DXd and T-DXd ( Fig 2B and 6A ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to address the difference between anti-CD47 and anti-SIRPα Abs in the T cell dependency. Apart from its role in suppressing macrophages, CD47 has been found to have various other functions [ 9 ]. For instance, CD47 has shown to be essential for the survival of T cells in mouse and human chimeric-antigen receptor T cells [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while CD47-SIRPα blockade showed impressive efficacy in some animal models, clinical efficacy is limited and especially poor for solid tumors 7 , 14 , 15 . Just recently, a late clinical trial of a CD47-blocking antibody was discontinued, and some other trials were also restrained 16 . Thus, at this time point, whether CD47-SIRPα blockade strategy can still be exploited for clinical advantage is facing a challenge.…”
Section: Introductionmentioning
confidence: 99%